The efficacy of forward and delayed feedback in recalling Intermediate first grade students scientific information (Journal of the College of Basic Education, 2023)
The current research aims to know the effectiveness of feedback: advanced and delayed in rememberingScientific information among the first intermediate grade students in general science. Reach a volumeThe sample is (134) male and female students, of whom (66) males and (68) females are in two schools, one of themfor males and the other for females were chosen randomly from among the middle and secondary schools located inBaquba city center. They assigned these students in advance to four groups, two for males and two forfor females. They were rewarded with (previous achievement in mathematics, general science, and chronological age).The experiment was carried out at the beginning of the second semester (2005-2006). The researcher prepared sixAchievement tests of the multiple choice type, the first was applied after the sample completed the studyThe first part of the academic subject, and so on for the rest of the parts. The researcher prepared a key to correct eachA test and the answers of the first group of males and females were corrected immediately after completion.of their answers to each test and the test papers were distributed to them and then withdrawn from them at the endThe lesson, which was called (Advanced Feedback). The answers of the second group were correctedmales and females, and it was distributed to them after a week, and it was withdrawn from them, which was named (Nutritiondelayed return). The teacher taught the subject in each school, and a remembrance test was prepared.Scientific information for which his paragraph was chosen from among the six test paragraphs, which have the bestEase coefficient and the highest discriminatory ability. The test was administered at the end of the two-month experiment.The t-test showed that no group was superior to the other of the two groups of males.and females.